John Hainsworth Mercer, 1922-1987 - Holdsworth, Gerald; Blake, Jr., Weston (ARCTIC, 1988)
From 1951 until 1954, Mercer studied at McGill University. His Ph.D. thesis, . was based on field work carried out in the vicinity of the Grinnell and Terra Nivea ice caps on southern Baffin Island. . Mercer was highly motivated by field work and literally thrived on it. Typically, and often to the chagrin of at least one of his contemporaries, Mercer did not unnecessarily burden himself (or others) with loads of data. Many of his papers seemed to be largely based on his unusual synthesizing and perceptive powers, supported, where necessary, by a few, but key, radioisotope dates. Mercer was not a compulsive lecturer - in fact, he shunned such "duties" - but for those of us at the institute as graduate students (of which G.H. was one) Mercer was frequently a source of both private inspiration and considerable amusement. An important paper in 1968 set in motion his and others' ideas on the dynamics of "marine ice sheets" (Mercer, 1968). . His realistic thinking through the ice sheet dynamics scenarios and the associated sea level changes inspired the numerical modellers to dedicate their paper to him. . The results of his field work are of great importance in synthesizing the spatial variations of global climate change, which was one of the underlying themes of Mercer's research. . His stimulating presence will be widely missed, especially by those at the Byrd Polar Research Center in Columbus, Ohio.